Comparative Analysis of Cantilever Retaining Wall and Retaining Wall with Relieving Platform. Issue 1 (July 2021) - Jiwankar, Himanshu; Mahule, Niraj; Jichkar, Rutvik; Dahiwale, Vaibhav; Dabhekar, Kuldeep; Khedikar, Isha; Agrawal, Rahul
Abstract: The concept and study of a cantilever retaining wall and a cantilever retaining wall with relieving platform with elevations varying from 5 to 8 meters and having a safe bearing capacity of 160 KN/m2 are presented in this paper. It also depicts relative research such as bending moment, safety against overturning and sliding, expense and economy, between the retaining walls. The cost and optimal cost are calculated as part of the relative analysis. Software and analytical results such as bending moment, deflection, and stresses are also discussed in this paper. Laterally acting total earth pressure is depicted to be reduced due to the provision of relieving platform (RP). The retaining wall with relieving platform (RW with RP) is shown to be cost-effective, more stable, and relieve the BM of the stem and heel portions than cantilever retaining wall (CRW). The findings of this research is drawn based on the results obtained using different models prepared in software, comparison of bending moments, requirement of tension reinforcement and these results are verified by manual analysis. The research shows that the CRW with RP is more economical and is more worthy than CRW.